Answer:
Explanation:
Given the equation:
![x^2+3x-7=0](https://img.qammunity.org/2023/formulas/mathematics/college/y1uy1fr01unfe4k1eipzjncxbasgwbb1ja.png)
On observation, the equation cannot be factorized, so we make use of the quadratic formula.
![x=(-b\pm√(b^2-4ac) )/(2a)](https://img.qammunity.org/2023/formulas/mathematics/college/30bplbkq52fdxqin3htbforzh2hmfylv9d.png)
Comparing with the form ax²+bx+c=0: a=1, b=3, c=-7
Substitute these values into the formula.
![x=\frac{-3\pm\sqrt[]{3^2-4(1)(-7)}}{2*1}](https://img.qammunity.org/2023/formulas/mathematics/college/sexr6zmfikc1v5tbfxy72724l3n4wa353v.png)
We then simplify and solve for x.
![undefined]()